Media Informasi Virtual Tour 3D Kawasan Konservasi Mangrove dan Bekantan Kota Tarakan - Sakila, Risma; Suprianto, Suprianto (Universitas Muhammadiyah Sorong, 2025)
In Tarakan City, there is a mangrove forest and proboscis monkey conservation area, which serves as a natural ecosystem where mangrove trees grow and various native fauna inhabit. So far, promotion has only relied on text and photos, which are not interactive. An interactive information medium, such as a 3D Virtual Tour, is a technology that can introduce tourist destinations more effectively. The application is designed using Unity Engine, 3ds Max, and Visual Studio Code to create scripts for the application. The Multimedia Development Life Cycle (MDLC) method is applied, consisting of six stages: concept, design, material collection, development, testing, and distribution, while UML (Unified Modeling Language) is used for documentation. A flowchart is also utilized to illustrate the application's process flow. The research results indicate that the virtual tour application represents the mangrove forest area and its objects as realistically as possible in 3D. This is evidenced by black box testing using the Likert scale, where 93.57% of 20 respondents provided positive feedback on the developed virtual tour application.